2023
DOI: 10.1002/chem.202203738
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[5]arene Derivatives Embedded with Aggregation‐Induced Emission Luminogens and Their Fluorescence Regulation

Abstract: Through McMurry coupling reaction, three mesoposition functionalized pillar[5]arene derivatives (H-1, H-2, and H-3) have been successfully prepared by embedding aggregation-induced emission luminogens (AIEgens, diphenyldibenzofulvene (DPDBF) and tetraphenylethylene (TPE)) into the skeleton of supramolecular macrocycles. H-1, bearing [1 5 ]paracyclophane ([1 5 ]PCP) and DPDBF moiety, exhibits yellow emission and demonstrates obvious AIE effect. In order to further improve the host-guest properties of this type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…A large number of compounds have been reported to exhibit the AIE features, including difluoroboron compounds, 10 pillar[5]arene derivatives, 11 organometallic complexes, 12 glyco-nanoparticles, 13 and some compounds with the tetraphenylethylene group, 14 triphenylamine (TPA) moiety, 15 and carbazole unit. 16 It is known that AIE-active compound usually possess the twisted molecular conformation, which is conducive to the formation of stimuli-responsive properties for exploring its potential application in inkless writing 17 and security paper.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of compounds have been reported to exhibit the AIE features, including difluoroboron compounds, 10 pillar[5]arene derivatives, 11 organometallic complexes, 12 glyco-nanoparticles, 13 and some compounds with the tetraphenylethylene group, 14 triphenylamine (TPA) moiety, 15 and carbazole unit. 16 It is known that AIE-active compound usually possess the twisted molecular conformation, which is conducive to the formation of stimuli-responsive properties for exploring its potential application in inkless writing 17 and security paper.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, reacting P5 with benzophenone in the presence of n -BuLi followed by dehydration gives a macrocycle with an alkene functionality at one belt position . While the number of compounds prepared through these approaches is very limited (Figure ), they have found use for photophysical applications ,, and in the synthesis of functional materials. ,, …”
Section: Introductionmentioning
confidence: 99%
“…30 Alternatively, reacting P5 with benzophenone in the presence of n-BuLi followed by dehydration gives a macrocycle with an alkene functionality at one belt position. 29 While the number of compounds prepared through these approaches is very limited (Figure 1), they have found use for photophysical applications, 29,30,[32][33][34][35] and in the synthesis of functional materials. 28,32,[36][37][38] While we are unaware of any reports of belt-functionalized pillar [6]arene (P6) macrocycles, Ma and co-workers recently reported that pillar [6]arene derivatives containing aryl groups directly attached to three of the belt positions could be synthesized via a stepwise synthesis.…”
Section: Introductionmentioning
confidence: 99%